2020
DOI: 10.1177/0007650320936974
|View full text |Cite
|
Sign up to set email alerts
|

How Do Large Purchasing Organizations Treat Their Diverse Suppliers? Minority Business Enterprise CEOs’ Perception of Corporate Commitment to Supplier Diversity

Abstract: Supplier diversity programs were created in the United States nearly 50 years ago to encourage private sector companies to provide business opportunities to underutilized minority business enterprises. In order to assess the experiences that minority business enterprise CEOs have with large purchasing organizations and their perceptions of justice and commitment of large purchasing organizations to the buyer–supplier relationship (BSR), this study utilizes survey data collected from 206 minority busin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…However, Zaefarian et al (2016) reported that only distributive and interactional justice increase commitment in the buyer–supplier relationship. Blount (2020) found that procedural justice has a negative on minority business enterprises' perceptions of buyers' commitment to the relationships. Jokela and Söderman (2017) extended the understanding of the fairness–commitment link by demonstrating a bidirectional relationship between fairness and commitment.…”
Section: Resultsmentioning
confidence: 99%
“…However, Zaefarian et al (2016) reported that only distributive and interactional justice increase commitment in the buyer–supplier relationship. Blount (2020) found that procedural justice has a negative on minority business enterprises' perceptions of buyers' commitment to the relationships. Jokela and Söderman (2017) extended the understanding of the fairness–commitment link by demonstrating a bidirectional relationship between fairness and commitment.…”
Section: Resultsmentioning
confidence: 99%
“…This paper introduces a more comprehensive definition of supplier diversity, beyond traditional spend with diverse suppliers as called for in literature (Yang et al , 2022). This paper introduces ways to reduce the risk of less than wholehearted adoption of supplier diversity by buyers (as pointed out by Blount, 2021), such as the bottoms-up program development. Further to that, this paper features ways to ensure wider stakeholder engagement in the program (as called for by Tate et al , 2010), through the use of ambassadors and nonprocurement leadership engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Supplier diversity finds its roots in US public procurement over 50 years ago (Blount, 2021). By requiring companies bidding for government contracts to allocate part of their external spend toward suppliers that have diverse ownership, the government sought to grow societal benefits from improved economic inclusion and economic activity for underrepresented constituencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance D&I, SD research should explore how the actions taken by buyers can impact counterparts and society (Gold and Schleper, 2017; Sordi et al ., 2022), and evaluate economic inclusion (Silva and Ruel, 2022; Sordi et al ., 2022). Otherwise, SD can be regarded as a buying company's promise regarding inclusiveness, while MS, mainly woman-owned, do not perceive that buyers are really committed to it (Blount, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%